Investigation of CO2 Orientational Dynamics through Simulated NMR Line Shapes** - Melix, Patrick; Heine, Thomas (ChemPhysChem, 2021)
The dynamics of carbon dioxide in third generation (i. e., flexible) Metal-Organic Frameworks (MOFs) can be experimentally observed by 13C NMR spectroscopy. The obtained line shapes directly correlate with the motion of the adsorbed CO2, which in turn are readily available from classical molecular dynamics (MD) simulations. In this article, we present our publicly available implementation of an algorithm to calculate NMR line shapes from MD trajectories in a matter of minutes on any current personal computer. We apply the methodology to study an effect observed experimentally when adsorbing CO2 in different samples of the pillared layer MOF Ni2(ndc)2(dabco) (ndc=2,6-naphthalene-dicarboxylate, dabco=1,4-diazabicyclo-[2.2.2]-octane), also known as DUT-8(Ni). In 13C NMR experiments of adsorbed CO2 in this MOF, small (rigid) crystals result in narrower NMR line shapes than larger (flexible) crystals. The reasons for the higher mobility of CO2 inside the smaller crystals is unknown. Our ligand field molecular mechanics simulations provide atomistic insight into the effects visible in NMR experiments with limited computational effort.
CRIS-Team Scopus Importer:2022-04-14
Keywords: CO2; DUT-8; line shape; metal-organic frameworks; molecular dynamics; NMR